Demystifying the Order from Above: Uganda versus the Attorney General, when the forces exceed their constitutional mandate - Lubogo, Isaac Christopher (Jescho Publishing House, 2021)
The law of criminal procedure lays down the machinery by which suspects are brought to court, tried and if found guilty, punished. Criminal procedure can also be defined as the means by which criminal law is enforced and involves the balancing of the liberty of the citizen against the interests of the community as a whole. The scope of criminal procedure extends over a wide perimeter from prevention and investigation of crime to prosecution and punishment of the offender. As far as human rights are concerned, every Ugandan citizen has a right to liberty. This presupposes that the freedom enjoyed by the citizens can only be limited according to the provisions of the law and anything done without heeding the same is said to be arbitrary. The Uganda Police Force is mandated under Section 4 of the Police Act to; protect the life, property and other rights of the individual, maintain security within Uganda, enforce the law, ensure public safety and order and detect and prevent crime in the society. In order to fulfill this mandate the Police is legally empowered to conduct arrests, searches and institute criminal proceedings. However, the in manner in which the Police has conducted numerous arrests over time, has left many Ugandans sceptical as to whether the Police is indeed a custodian of law and order. Many have witnessed brutal arrests of politicians, on television and in newspapers over time and even more recently when Police was dispersing people from political consultative sessions of presidential opposition candidates like Amama Mbabazi and Kiiza Besigye. The question that continues to linger is how should these arrests be conducted under the law? Benjamin Odoki, in his book, Justice: A Guide to Criminal Procedure in Uganda, 1990, analyses the aspect of arrests by the government. It discusses the procedure of an arrest as enshrined in the laws of Uganda, the rights of an accused person, a suspect and even a convict. The book, in principle, analyses the time before an arrest is carried out; the time and manner of the arrest; and the events that follow the arrest. The book discusses the Miranda rule that guarantees that persons detained by police will not be interrogated in a way that places them at a disadvantage. The book also explores the aspect of searches on people’s property; how and when these searches should be conducted in accordance with the law. The book demystifies the highly volatile discussion of use of reasonable force while carrying out arrests. It lays out the threshold of what amounts to reasonable force and envisages circumstances where force is necessary to effect and arrest. The book also sheds light on the fundamental presumption of innocence and how this presumption should ordinarily be treated. Consequently, the book highlights the abuses that have and can be occasioned following the disregard or misunderstanding of this notion. The book reviews the principle of preventive arrest in light of human rights and its use as a tool of oppression. The book also labours to demystify the difference between the different armed groups in the country. It majorly indicates the difference between the police and the army and how their roles are different. It postulates the instances where this thin line of difference has been overstepped by either group and how catastrophic this action has proven to be overtime. It elaborates on the Posse Comitatus principle that argues against any military intrusion into civilian affairs. The book also tries to put into perspective the different groups being formed and revived in the country in the guise of maintaining law, peace and order. These groups include the Local Defence Units, Crime preventers and the like. The book attempts to place them under the different laws promulgated for the governance of the people of Uganda. The book also concerns itself with the aspect of obtaining confessions and admissions from arrested persons for purposes of presenting the same as evidence before courts of law. There have been instances where arrested persons have been coerced into confessions which have led to false imprisonments. The book also discusses aspects of finding no case against arrested people and the notion of nolle proseque; and the aspect of compensation for the people that have been falsely convicted or wrongfully arrested. The book discusses the issue of liability for police brutality. It discusses the vicarious liability of the Government in civil proceedings as master and employer of police officers for acts of police officers done within the course of duty. The book also considers personal liability of Police officers for their reckless acts in law enforcement and the possibility of the Police opening up investigations and commencing criminal proceedings against its officers. As a bonus, the book briefly discusses part of civil law that is relevant to the issues enunciated above.
Keywords: Criminal law - Uganda; Criminal procedure - Uganda